DNA barcoding of fish fauna from low order streams of Tapajós River basin - Guimarães, Karen Larissa Auzier; Sousa, Marcos Paulo Alho de; Ribeiro, Frank Raynner Vasconcelos; Porto, Jorge Ivan Rebelo; Rodrigues, Luís Reginaldo Ribeiro (PLoS ONE, 2018)
The Amazon basin harbors a megadiverse fish fauna spread in an intricate network of big rivers and small streams. The Amazonian streams are home of many small sized fishes that remains poorly documented. In order to accelerate the scientific knowledge on these important aquatic systems we adopted a modern integrative approach joining morphology and molecular tools to investigate the ichthyofauna assemblages from low order streams situated on the lower Tapajós River Basin. Cytochrome c Oxidase I (COI) DNA barcodes from 252 specimens collected from 10 stream sites were obtained. The combined analysis revealed 29 species, 21 genera and 11 families. Cryptic diversity was evidenced in Knodus sp.1, Aequidens epae and Copella callolepis, in which deep genetic divergence were detected (intraspecific distances: 20.48%, 7.99% and 3.77%, respectively). The putative new species showed closer relationships with their counterparts occurring in the Tapajós-Xingu water drainages. © 2018 Guimarães et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.
Keywords: Aequidens Epae; Chordata; Coi Gene; Controlled Study; Copella Callolepis; Dna Barcoding; Fauna; Gene; Gene Sequence; Genetic Distance; Genetic Variability; Intraspecific Distance; Knodus; Nonhuman; River Basin; Stream (river); Water Supply; Animals; Biodiversity; Environmental Protection; Fish; Genetics; Phylogeny; River; Cytochrome C Oxidase; Fish Protein; Animalss; Biodiversity; Conservation Of Natural Resources; Dna Barcoding, Taxonomic; Electron Transport Complex Iv; Fish Proteins; Fishes; Phylogeny; Rivers